COVID-19: co musimy wiedzieć o delirium stanu ciężkiego podczas trwania pandemii SARS-CoV-2? - Kotfis, Katarzyna; Williams Roberson, Shawniqua; Wilson, Jo; Pun, Brenda; Ely, E. Wesley; Jeżowska, Ilona; Jezierska, Maja; Dabrowski, Wojciech (Anestezjologia Intensywna Terapia, 2020)
In March 2020, the World Health Organisation announced the COVID-19 pandemic caused by the SARS-CoV-2 virus. As well as respiratory failure, the SARS-CoV-2 may cause central nervous system (CNS) involvement, including delirium occurring in critically ill patients (ICU delirium). Due attention must be paid to this subject in the face of the COVID-19 pandemic. Delirium, the detection of which takes less than two minutes, is frequently underestimated during daily routine ICU care, but it may be a prodromal symptom of infection or hypoxia associated with severe respiratory failure. During the COVID-19 pandemic, systematic delirium monitoring using validated tests (CAM-ICU or ICDSC) may be sacrificed. This is likely to be due to the fact that the main emphasis is placed on organisational issues, i.e. the lack of ventilators, setting priorities for limited mechanical ventilation options, and a shortage of personal protective equipment. Early identification of patients with delirium is critical in patients with COVID-19 because the occurrence of delirium may be an early symptom of worsening respiratory failure or of infectious spread to the CNS mediated by potential neuroinvasive mechanisms of the coronavirus. The purpose of this review is to identify problems related to the development of delirium during the COVID-19 epidemic, which are presented in three areas: i) factors contributing to delirium in COVID-19, ii) potential pathophysiological factors of delirium in COVID-19, and iii) long-term consequences of delirium in COVID-19. This article discusses how healthcare workers can reduce the burden of delirium by identifying potential risk factors and difficulties during challenges associated with SARS-CoV-2 infection.